A NEW APPROACH TO THE ASSESSMENT OF PSYCHOLOGICAL READINESS FOR HIGHER EDUCATION (THE EXAMPLE OF PREVENTIVE MEDICINE FACULTY STUDENTS AT PACIFIC STATE MEDICAL UNIVERSITY) - О. B. Asriyan; R. V. Kadyrov; V. V. Chernenko (Вестник Кемеровского государственного университета, 2013)
The article discusses a new approach to the assessment of psychological readiness for learning through the study of the level of higher education students’ social and emotional intelligence development. Personality features, motivation, emotional and social intelligence of Pacific State Medical University students (138 people) are analysed. The necessity of introducing innovative education forms in the education process and that of organizing annual team building activities for freshmen are proved.